Wood anatomy and physical properties of the wood and bark in Betula nana growing in Finland. - Bhat, K.; Kärkkäinen, Matti (Silva Fennica, 1982)
Eighty samples were collected from three swamp sites. In the butt portion of the dwarf shrub the average number of growth rings was 12 and the average diameter of the sprouts 6 mm. The basic density of wood was 457 kg/m and that of bark 544 kg/m. The proportion of bark was 32â38% of weight or volume. The vessel elements and fibres were short and their diameter small. The proportion of vessels was 15%, that of fibres 70% and that of rays 15%.Betula nana33